Knowledgeably responding to reasons - Cunningham, J (Springer Netherlands, 2018)
Jennifer Hornsby has defended the Reasons-Knowledge Thesis (RKT): the claim that Φ-ing because p requires knowing that p, where the ‘because’ at issue is a rationalising ‘because’. She defends (RKT) by appeal to the thought that it provides the best explanation of why the subject in a certain sort of Gettier case fails to be in a position to Φ because p. Dustin Locke and, separately, Nick Hughes, present some modified barn-façade cases which (a) seem to constitute counterexamples to (RKT) and (b) undermine Hornsby’s way of motivating it by rendering their alternative Reasons-Explanation Thesis (RET) a better explanation of Hornsby’s datum. This paper defends (RKT) and Hornsby’s argument for it against those objections. First, I point out that their supposedly intuitive verdict about the relevant barn-façade cases is not as intuitive as they think. Second, I point out that even if we share the intuition: we have strong reason to doubt the verdict anyway. And finally, I point out that since (RET) is independently implausible, the two problems can be tackled anyway.